2001
DOI: 10.1111/j.1365-2109.2001.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Tagging: on the use of passive integrated transponder (PIT) tags for the identification of fish

Abstract: To determine the ef®cacy of passive integrated transponder (PIT) tags for marking rohu Labeo rohita (Ham.) in the selective breeding programme, a series of experiments has been carried out at the Central Institute of Freshwater Aquaculture (CIFA) under the Indo±Norwegian project of`Selective breeding of rohu'. Six groups of rohu ®ngerlings with weight ranging from 2 g to 20 g were tagged with PIT tags to determine a suitable size range for tagging. Fingerlings weighing 8±15 g were found to be quite suitable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 5 publications
2
29
1
Order By: Relevance
“…Additionally, the fish were obviously vital, no signs of diseases were observed and neither ulcers and bleedings nor other signs of intraabdominal inflammation were found within the abdominal cavity during evisceration. These findings are in concordance with several previous studies in other species (Baras et al 2000, Das Mahapatra et al 2001, Acolas et al 2007. Based on these results, it can be concluded that the intraabdominal implantation of PIT tags has no negative effects on animal health and performance in turbot.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, the fish were obviously vital, no signs of diseases were observed and neither ulcers and bleedings nor other signs of intraabdominal inflammation were found within the abdominal cavity during evisceration. These findings are in concordance with several previous studies in other species (Baras et al 2000, Das Mahapatra et al 2001, Acolas et al 2007. Based on these results, it can be concluded that the intraabdominal implantation of PIT tags has no negative effects on animal health and performance in turbot.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, a simple and reliable individual identification method is required that does not affect animal health, is easy to handle and provides a large number of different identifications. In many species, radio frequency identification systems are an adequate alternative to meet these requirements (Baras et al 2000, Das Mahapatra et al 2001, Navarro et al 2006, Hopko et al 2010. In the present study, we applied PIT tags to almost 6 000 turbots.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No detrimental effect has been found on survival (Bolland, Cowx, & Lucas, 2009;Navarro et al, 2006;Ombredane, Baglinière, & Marchand, 1998), growth (Acolas, Roussel, Lebel, & Baglinière, 2007;Knaepkens, Maerten, Tudorache, De Boeck, & Eens, 2007;Lee, Park, & Cho, 2009), reproduction (Baras, Malbrouck, Houbart, Kestemont, & Mélard, 2000;Mahapatra et al, 2001), feeding behavior (Newby, Binder, & Stevens, 2007;, and swimming ability (Moore, Russell, & Potter, 1990;Mueller, Moursund, & Bleich, 2006;). The few studies on snakes have shown that PIT-tagging does not affect growth, movement, and speed (Keck, 1994;Jemison et al, 1995).…”
mentioning
confidence: 99%